2013
DOI: 10.1021/ct400323z
|View full text |Cite
|
Sign up to set email alerts
|

A Quadratically-Converging Nudged Elastic Band Optimizer

Abstract: Nudged elastic band (NEB) is a well established chain-of-states method to locate the minimum energy path in configuration space. Unfortunately, existing search algorithms suffer from slow convergence. We provide an analytic derivative of the nudged elastic band force, enabling a full Newton-Raphson optimization. For molecular systems, the components of the step belonging to translations and rotations are removed with an efficient algorithm. Minimization of the NEB force is ensured by reversing components for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…The images along the NEB path were optimized to the minimum energy path (MEP) through a force projection procedure, in which the potential forces act perpendicular to the path whereas the spring forces act along the path. [31][32][33][34] Free Energy Calculations along the NEB Reaction Path. The potential of mean 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 7 force (PMF) along the above NEB optimized path, min r v , was obtained by computing the free energy difference,…”
Section: Qm/mmmentioning
confidence: 99%
“…The images along the NEB path were optimized to the minimum energy path (MEP) through a force projection procedure, in which the potential forces act perpendicular to the path whereas the spring forces act along the path. [31][32][33][34] Free Energy Calculations along the NEB Reaction Path. The potential of mean 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 7 force (PMF) along the above NEB optimized path, min r v , was obtained by computing the free energy difference,…”
Section: Qm/mmmentioning
confidence: 99%
“…Previously, 43 we have shown that the analytic Jacobian of the NEB force, the matrix of derivatives of the NEB force with respect to the coordinates, can be used to significantly improve the convergence of a NEB minimization in a Newton-Raphson-like manner.…”
Section: Nudged Elastic Band In the Free Energy Surfacementioning
confidence: 99%
“…It contains 6 components corresponding to translation and rotation. 43 Thus, it is singular and cannot directly be inverted to form a Newton-Raphson step of the form…”
Section: Nudged Elastic Band In the Free Energy Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…An approach by Bohner et.al. 8 for removing rotation and translation from an NEB calculation relies on modifying the energy minimization algorithm by eliminating the six 5 smallest eigenvalues of the Jacobian matrix of NEB forces. This approach has good convergence properties but is computationally quite demanding since it requires finding the eigenvalues at each iteration.…”
Section: Introductionmentioning
confidence: 99%